2023
DOI: 10.1029/2022gl102383
|View full text |Cite
|
Sign up to set email alerts
|

Pore‐Scale Observations of Hydrogen Trapping and Migration in Porous Rock: Demonstrating the Effect of Ostwald Ripening

Abstract: We use high‐resolution three‐dimensional X‐ray imaging to study hydrogen injection and withdrawal in the pore space of Bentheimer sandstone. The results are compared with a replicate experiment using nitrogen. We observe less trapping with hydrogen because the initial saturation after drainage is lower due to channeling. Remarkably we observe that after imbibition, if the sample is imaged again after 12 hr, there is a significant rearrangement of the trapped hydrogen. Many smaller ganglia disappear while the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This is detrimental to the H 2 withdrawal process, and as a result, it can be inferred that the use of strongly water-wet Gosford sandstone may not be a suitable option for hydrogen storage due to the snap-off effects that encourage the high residual H 2 trapping and discourage the extraction or withdrawal of stored H 2 . Zhang et al 65 reported that H 2 recovery efficiency could be enhanced by the swelling of larger ganglia, which can increase the gas connectivity and result in less hysteresis.…”
Section: Resultsmentioning
confidence: 99%
“…This is detrimental to the H 2 withdrawal process, and as a result, it can be inferred that the use of strongly water-wet Gosford sandstone may not be a suitable option for hydrogen storage due to the snap-off effects that encourage the high residual H 2 trapping and discourage the extraction or withdrawal of stored H 2 . Zhang et al 65 reported that H 2 recovery efficiency could be enhanced by the swelling of larger ganglia, which can increase the gas connectivity and result in less hysteresis.…”
Section: Resultsmentioning
confidence: 99%
“…The polymer spheres contain hydrogen. The role of hydrogen in Ostwald ripening has only occasionally been investigated [76] but is considered to be an important part of the desalination process [73].…”
Section: Ostwald Ripening Model Analysismentioning
confidence: 99%
“…Two‐phase flow in porous media is a critical area in many scientific fields and applications (Bear & Cheng, 2010; Blunt, 2017, 2022; Boot‐Handford et al., 2014; Juanes et al., 2006; Li et al., 2023; Moghadasi et al., 2023; Sahimi, 2011; Shokri‐Kuehni et al., 2017; Zhang et al., 2023c; Zhao, 2013). Many porous materials, from electrochemical devices to catalysts and porous rocks, have a wide range of pore size.…”
Section: Introductionmentioning
confidence: 99%